Anwachsungsprinzip 2.0 Die Anwachsung der Mitgliedschaft als allgemeines, rechtsformübergreifendes Prinzip des Gesellschaftsrechts? - Pechtl, Maximilian (Mohr Siebeck, 2022)
Partnership law is evolving. Maximilian Pechtl examines how the latest dogmatic developments impact the significance of one of the basic principles of partnership law: the so-called principle of accrual. He shows how, from this, it is possible to formulate a general principle of corporate law which also encompasses joint stock corporations.
PublicationDate: 20220830
Keywords: Gesellschaftsrecht -- Juristische Person -- Gesamthand -- Diskriminierungsverbote -- Gesetz zur Modernisierung des Personengesellschaftsrechts (MoPeG) -- Beginning -- Gesellschafterwechsel -- Ressourcen -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht